2016
DOI: 10.1038/nrn.2016.138
|View full text |Cite
|
Sign up to set email alerts
|

Integrins in synapse regulation

Abstract: Integrins are a large family of extracellular matrix (ECM) receptors. In the developing and adult brain, many integrins are present at high levels at synapses. The tetrapartite structure of synapses - which comprises presynaptic and postsynaptic neurons, the ECM and glial processes - places synaptic integrins in an excellent position to sense dynamic changes in the synaptic environment and use this information to coordinate further changes in synapse structure and function that will shape neural circuit proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
150
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(156 citation statements)
references
References 156 publications
3
150
0
1
Order By: Relevance
“…Some integrin subunits, such as b3, are enriched at synapses (Pinkstaff et al, 1999;Chavis & Westbrook, 2001;Chan et al, 2003;Shi & Ethell, 2006) and have been involved in GluA2-containing AMPAR trafficking (Cingolani et al, 2008;Pozo et al, 2012). To define whether integrins control AMPAR trafficking either directly or through downstream signaling pathways (Pozo et al, 2012;Park & Goda, 2016), we focused on the possible involvement of ERK1/2. To define whether integrins control AMPAR trafficking either directly or through downstream signaling pathways (Pozo et al, 2012;Park & Goda, 2016), we focused on the possible involvement of ERK1/2.…”
Section: Of 20mentioning
confidence: 99%
See 1 more Smart Citation
“…Some integrin subunits, such as b3, are enriched at synapses (Pinkstaff et al, 1999;Chavis & Westbrook, 2001;Chan et al, 2003;Shi & Ethell, 2006) and have been involved in GluA2-containing AMPAR trafficking (Cingolani et al, 2008;Pozo et al, 2012). To define whether integrins control AMPAR trafficking either directly or through downstream signaling pathways (Pozo et al, 2012;Park & Goda, 2016), we focused on the possible involvement of ERK1/2. To define whether integrins control AMPAR trafficking either directly or through downstream signaling pathways (Pozo et al, 2012;Park & Goda, 2016), we focused on the possible involvement of ERK1/2.…”
Section: Of 20mentioning
confidence: 99%
“…Of note, incubation of neurons with a specific anti-integrin b1-monoclonal antibody (aCD29) completely prevented the PTX3-dependent increase of synaptic GluA content ( Fig 4A and B), indicating that b1-containing integrins are involved in the process of AMPARs recruitment induced by PTX3. To define whether integrins control AMPAR trafficking either directly or through downstream signaling pathways (Pozo et al, 2012;Park & Goda, 2016), we focused on the possible involvement of ERK1/2. In line with an increased levels of phospho-ERK1/2 in neurons upon PTX3 application ( Fig 4C), blockade of ERK1/2 phosphorylation through the specific MEK1 inhibitor, PD98059, completely prevented the PTX3-induced increase of mEPSC frequency and amplitude ( Fig 4D-F) as well as the synaptic ▸ Figure 3.…”
Section: Ptx3-dependent Ampar Clustering Requires An Intact Perineuramentioning
confidence: 99%
“…We tested if integrin class adhesion proteins, which co-operate with CB 1 R in actin regulatory signaling in cultured cells (Dalton et al 2013), fill this critical role. Integrins are dimeric transmembrane adhesion receptors for extracellular matrix and cell surface proteins that are expressed throughout the brain by neurons and glia (Park and Goda 2016). In hippocampus the majority of integrins contain the β1 subunit (Pinkstaff et al 1999) and β1 integrins have been localized to both pre-and postsynaptic compartments (Schuster et al 2001;Park and Goda 2016).…”
Section: Cb 1 R Signaling In Lpp Terminalsmentioning
confidence: 99%
“…Integrins are dimeric transmembrane adhesion receptors for extracellular matrix and cell surface proteins that are expressed throughout the brain by neurons and glia (Park and Goda 2016). In hippocampus the majority of integrins contain the β1 subunit (Pinkstaff et al 1999) and β1 integrins have been localized to both pre-and postsynaptic compartments (Schuster et al 2001;Park and Goda 2016). We previously demonstrated that, in hippocampal slices, infusion of β1 neutralizing antisera disrupts activity-induced actin polymerization and LTP in field CA1 (Kramar et al 2006).…”
Section: Cb 1 R Signaling In Lpp Terminalsmentioning
confidence: 99%
“…Most of the integrins have long extracellular domains which bind to ECM ligands such as fibronectin and laminin, and short cytoplasmic domains of about 60 amino acids, which link their receptors to the cytoskeleton. The extracellular domain of alpha1 integrin contains seven homologous repeats of about 30 to 40 amino acids with 20-30 amino-acid stretch in between followed and three cation-binding sequences [21,22]. The TMD with 25-amino acid sequence will be used as the peptide to target stem cells and the 28 amino-acid signal peptide will be utilized to direct the peptide to the plasma membrane.…”
Section: Alpha1mentioning
confidence: 99%